EMBODIED DIGITAL PROTEST IN ROBLOX: A MULTIMODAL CRITICAL DISCOURSE ANALYSIS OF POWER AND RESISTANCE IN VIRTUAL ACTIVISM - Putri Rizki Syafrayani; Siti Aisah Ginting; Winda Setiasari (English Education Department at FKIP Nommensen University, 2026)
This study investigates the construction of meanings of power and protest through multimodal semiotic resources within the “Free Palestine” protest simulation on the Roblox video game platform. Roblox enables users to perform protest discourse through embodied interaction, spatial navigation, symbolic representation, and multimodal participation as participatory virtual environments increasingly function as sociopolitical communicative spaces. This research applies the MCAD by Jewitt and Machin and Mayr to examine how linguistic, visual, gestural, spatial, and auditory semiotic resources interact to construct representations of resistance, solidarity, and institutional authority within the virtual environment. Data were collected through repeated close-playing observation, multimodal logging, field-note documentation, and iterative analysis of representative protest scenes. The analytical process involved multimodal categorization, interpretive coding, and critical examination of how semiotic resources operate relationally across interactive gameplay contexts. The findings demonstrate that protest discourse within Roblox is enacted through embodied and participatory performance in which players negotiate ideological positioning through avatar movement, spatial confrontation, and symbolic alignment. This study contributes theoretically to MCDA by extending multimodal discourse analysis beyond static media texts to interactive gaming environments characterized by embodied resistance and participatory protest discourse.